2018
DOI: 10.5994/jei.14.3.152
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh keberadaan habitat alami terhadap keanekaragaman dan kelimpahan serangga pengunjung bunga mentimun

Abstract: Keberadaan serangga pada suatu habitat pertanian dipengaruhi oleh beberapa faktor salah satunya adalah habitat alami. Tujuan penelitian ini adalah untuk mempelajari pengaruh jarak habitat alami terhadap keanekaragaman dan kelimpahan serangga pengunjung bunga pada pertanaman mentimun. Penelitian dilakukan di lahan mentimun pada 12 lokasi yang terletak di Kabupaten Bogor, Cianjur, dan Sukabumi, Jawa Barat. Jarak habitat alami dengan lahan pertanian dikategorikan dalam dua kelompok, yaitu dekat dengan hab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
1
5
0
2
Order By: Relevance
“…The cayenne fields in Salodik Village are located close to natural habitats, so this condition is likely to cause a high number of insects visiting cayenne flowers. The distance between natural/semi-natural habitats and cayenne fields affects the diversity of insect species that visit cayenne flowers (Susilawati et al, 2017). In agricultural landscapes, semi-natural habitats are a significant driver of flower visitor insect diversity (Garibaldi et al, 2011;Scheper et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cayenne fields in Salodik Village are located close to natural habitats, so this condition is likely to cause a high number of insects visiting cayenne flowers. The distance between natural/semi-natural habitats and cayenne fields affects the diversity of insect species that visit cayenne flowers (Susilawati et al, 2017). In agricultural landscapes, semi-natural habitats are a significant driver of flower visitor insect diversity (Garibaldi et al, 2011;Scheper et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In agricultural landscapes, natural or semi-natural habitats can provide habitats for wild insects (Kennedy et al, 2013;Morandin & Kremen, 2013), nesting sites (Öckinger & Smith, 2007), and resources, including food sources for flower-visiting insects, even natural or semi-natural habitats can maintain food sources throughout the season (Cole et al, 2017;Requier et al, 2020). In addition, the presence of natural habitats (Kleijn & van Langevelde, 2006;Susilawati et al, 2017) and flowering plants around the plantations affect flower visitor insects and pollinating insects (Sataral et al, 2022). The ecological services provided by flower visitor insects for crop production have been recognized, especially in cultivated plants growing near natural habitats as opposed to those far from natural habitats (Bailey et al, 2014;Halinski et al, 2018;Hipólito et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The landscape structure could cause the high abundance of Parasitic Hymenoptera in tidal swamp rice cultivation. The diversity and abundance of Hymenoptera in an agricultural habitat can be influenced by landscape structure (Susilawati 2016). Ikhsan et al (2020) also reported that the abundance of Parasitic Hymenoptera in tidal swamp rice was higher in complex landscapes than in simple landscapes.…”
Section: Diversity and Abundance Of Parasitic Hymenoptera On Tidal Sw...mentioning
confidence: 99%
“…Presence of Parasitic Hymenoptera on tidal swamp rice can be affected by the structure of the landscape. The landscape structure and habitat conditions can influence the diversity and abundance of Hymenoptera in an agricultural habitat (Susilawati 2016). Lizmah (2015) reported that the abundance of Hymenoptera parasitoid in cucumber (Cucumis sativus) cultivation was higher in complex landscapes than in simple landscapes.…”
Section: Correlation Of Parasitic Hymenoptera With Their Landscapesmentioning
confidence: 99%